2014
DOI: 10.1002/pssa.201431239
|View full text |Cite
|
Sign up to set email alerts
|

Mutual interaction of N, B, and O during heteroepitaxial diamond growth: Triggering the nitrogen induced growth acceleration

Abstract: The mutual interaction of N, B, and O during heteroepitaxial diamond growth by microwave plasma chemical vapour deposition (MPCVD) is investigated. The study comprises in situ growth rate measurements by laser reflection interferometry (LRI) and the monitoring of impurity containing gas phase species like CN and BH by optical emission spectroscopy (OES). In the gas phase, among the combinations (N, B), (N, O), and (B, O) only the latter pair shows a measurable mutual influence. In contrast, growth rate measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…In their study, this behavior was attributed to an expansive stress induced by nitrogen. The latter could be the same reason in our case but other phenomena such us the surface reorganization suggested by Sartori and coworkers and discussed in the previous paragraphs . Consequently, the introduction of nitrogen in the gas mixture permits to partially compensate the strain induced by the boron incorporation.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…In their study, this behavior was attributed to an expansive stress induced by nitrogen. The latter could be the same reason in our case but other phenomena such us the surface reorganization suggested by Sartori and coworkers and discussed in the previous paragraphs . Consequently, the introduction of nitrogen in the gas mixture permits to partially compensate the strain induced by the boron incorporation.…”
Section: Resultssupporting
confidence: 82%
“…Such behavior can be attributed to the difference of the atom radius of carbon, boron, and nitrogen. We could also attribute this effect to the reorganization of the growth surface due to the presence of nitrogen as already suggested in a previous study . Codoping thus appears as a useful strategy for producing improved p + substrates that are potentially suitable for the development power electronics.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…The stereochemistry of these localities and edges is different from a (100) surface looking rather like (111), (113), or even (110) surfaces [64][65][66]. Additionally, it has been observed by many groups that trace additions of nitrogen (0 to 10 ppm) to the gas reactants can dramatically increase the growth rate and change the surface morphology [67,68]. A mechanism of the catalytic role of N for the growth rate on (111) surfaces has been discussed in [69].…”
Section: Nitrogen Dopingmentioning
confidence: 98%
“…Meanwhile, by comparing the three growth rates obtained under the gas condition of Mode #6, it can be seen that the original nitrogen doping has significantly increased the growth rate, while the supplementary nitrogen doping experiment just further increased that. Sartori et al have reported that there is a nitrogen concentration threshold regulating effect on the growth rate of nitrogen doped diamond in the presence of 10 −2 -10 −1 ppm of low boron impurity concentration in the chamber [50]. It means that under low nitrogen flow rate, the acceleration effect of nitrogen on diamond growth can be canceled by the presence of boron.…”
Section: Resultsmentioning
confidence: 99%